A randomised controlled trial of the effectiveness of soft silicone multi‐layered foam dressings in the prevention of sacral and heel pressure ulcers in trauma and critically ill patients: the border trial. Issue 3 (27th May 2013) - Santamaria, Nick; Gerdtz, Marie; Sage, Sarah; McCann, Jane; Freeman, Amy; Vassiliou, Theresa; De Vincentis, Stephanie; Ng, Ai Wei; Manias, Elizabeth; Liu, Wei; Knott, Jonathan
Abstract The prevention of hospital acquired pressure ulcers in critically ill patients remains a significant clinical challenge. The aim of this trial was to investigate the effectiveness of multi‐layered soft silicone foam dressings in preventing intensive care unit (ICU) pressure ulcers when applied in the emergency department to 440 trauma and critically ill patients. Intervention group patients (n = 219) had Mepilex® Border Sacrum and Mepilex® Heel dressings applied in the emergency department and maintained throughout their ICU stay. Results revealed that there were significantly fewer patients with pressure ulcers in the intervention group compared to the control group (5 versus 20, P = 0·001). This represented a 10% difference in incidence between the groups (3·1% versus 13·1%) and a number needed to treat of ten patients to prevent one pressure ulcer. Overall there were fewer sacral (2 versus 8, P = 0·05) and heel pressure ulcers (5 versus 19, P = 0·002) and pressure injuries overall (7 versus 27, P = 0·002) in interventions than in controls. The time to injury survival analysis indicated that intervention group patients had a hazard ratio of 0·19 (P = 0·002) compared to control group patients. We conclude that multi‐layered soft silicone foam dressings are effective in preventing pressure ulcers in critically ill patients when applied in the emergency department prior to ICU transfer.